Self-assessed versus statistical evidence of labour market discrimination: The case of indigenous Australians - Alan Duncan; Astghik Mavisakalyan; Yashar Tarverdi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We assess the relative importance of statistical residual-based measures of discrimination in determining indigenous Australians' perceptions of discrimination in the labour market. We find that statistical measures are largely unrelated to discrimination reports among males and negatively related to discrimination reports among females. Our results further indicate that the discrepancy between statistical and self-reported measures of discrimination is larger among individuals with stronger indigenous cultural identity. Our findings point at the potential significance of 'nonstatistical' evidence of discrimination, and underscore the importance of asking indigenous people directly about their experiences when addressing the issue of indigenous labour market disadvantage.
Keywords: J15; J21; J71; 330; ethnic discrimination; employment; Australia